2005
DOI: 10.1172/jci23360
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelium is critically involved in the hypotensive and hypovolemic actions of atrial natriuretic peptide

Abstract: Atrial natriuretic peptide (ANP), via its vasodilating and diuretic effects, has an important physiological role in the maintenance of arterial blood pressure and volume. Its guanylyl cyclase-A (GC-A) receptor is highly expressed in vascular endothelium, but the functional relevance of this is controversial. To dissect the endothelium-mediated actions of ANP in vivo, we inactivated the GC-A gene selectively in endothelial cells by homologous loxP/Tie2-Cre-mediated recombination. Notably, despite full preservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 46 publications
(80 reference statements)
11
151
0
4
Order By: Relevance
“…Hematocrit for both genotypes was in the upper normal range 30 and was not different between AtrapϪ/Ϫ and ϩ/ϩ mice, as reported before for other models of chronic volume expansion. 31,32 PRC and, by inference, renin secretion were suppressed in AtrapϪ/Ϫ mice. The absence of Atrap from renin-generating granular cells of the afferent arteriole indicates the operation of an indirect effect on renin secretion in AtrapϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 84%
“…Hematocrit for both genotypes was in the upper normal range 30 and was not different between AtrapϪ/Ϫ and ϩ/ϩ mice, as reported before for other models of chronic volume expansion. 31,32 PRC and, by inference, renin secretion were suppressed in AtrapϪ/Ϫ mice. The absence of Atrap from renin-generating granular cells of the afferent arteriole indicates the operation of an indirect effect on renin secretion in AtrapϪ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous studies have demonstrated the effectiveness of using the Tie2-Cre mice to selectively delete floxed genes in cells of endothelial lineage. [30][31][32] Myelomonocytic-specific deletion of TFPI-K1 was achieved by crossing the TFPI Flox mice with transgenic mice expressing Cre recombinase under control of the LysM promoter (LysM-Cre). The resulting offspring were backcrossed to TFPI Flox homozygosity while maintaining the LysM-Cre transgene (TFPI LysM ).…”
Section: Generation Of Mice With Cell-specific Deletion Of the Tfpi-kmentioning
confidence: 99%
“…Utilizing a similar strategy, Sabrane, Kuhn, and coworkers have now used a loxP/Tie2-Cre recombination system to selectively delete the gene for GC-A in mouse vascular endothelium (6). The authors show that the direct vasodilating effects of ANP on isolated arteries and apparently normal renal function were preserved in endothelial cell-specific GC-A knockout mice; however, the animals still exhibited a hypertensive phenotype with expanded vascular volume and cardiac hypertrophy.…”
Section: Renal Versus Endothelial Mechanisms In Regulating Plasma Volumementioning
confidence: 99%